Health care seeking behavior for common childhood illnesses in Birendranagar municipality, Surkhet, Nepal: 2018. - Ganga Tiwari; Ajoy Kumar Thakur; Sushil Pokhrel; Ganesh Tiwari; Durga Prasad Pahari (PLoS ONE, 2022)
Background Appropriate and prompt health care seeking by parents or caretakers can reduce morbidity and mortality among under-five year children. Although remarkable progress has been made in the reduction of under-five mortality, still the under-five mortality rate is high in Nepal. There are few studies on health care seeking behavior among caretakers in Nepal. Therefore, this study was conducted to determine the prevailing health care seeking behavior of caretakers on common childhood illness of under five year children and to identify the association of socio demographic, economic, illness related and health system related factors with health care seeking behavior in 2018. Methods A community based descriptive cross-sectional study was conducted from September to November 2018. Data were collected using a pretested semi-structured interview schedule. Both descriptive and inferential statistics were used to present the data. Bivariate and multivariate logistic regression analysis was used to identify the factors associated with health care seeking behavior. Results A total of 387 caretakers participated in the study. Of these, 84.8% sought any type of care and 15.2% did nothing. Amongst those who sought care 42.4% visited the pharmacy directly, 25.3% visited the health facility. Amongst those who visited a health facility, 37.2% of caretakers sought prompt health care. Common danger sign stated by caretakers was fever in children (92.4%). Secondary education(AOR = 0.357, 95%CI = 0.142-0.896), involvement in service as an occupation(AOR = 3.533, 95%CI = 1.096-11.384), distance to reach nearest health facility(0.957, 95%CI = 0.923-0.993) and perceived severity of illness; moderate severity (7.612, 95%CI = 2.127-27.242), severe severity (AOR = 15.563, 95%CI = 3.495-69.308) were found to be significantly associated with health care seeking behavior. Conclusion Strong policies and regulations should be formulated and implemented at Birendranagar municipality of Surkhet district to prevent direct purchase of medicines from pharmacies without any consultation. It is essential to conduct the health awareness program at community level on early recognition of danger signs and importance of consulting health facilities.